1988
DOI: 10.1002/1097-0142(19881015)62:8<1511::aid-cncr2820620811>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic production of salivary-type amylase by a lga-λ-type multiple myeloma

Abstract: A patient with IgA-lambda-type multiple myeloma who appeared to be secreting salivary-type amylase ectopically is reported. Both the patient's serum and urine contained high levels of amylase. Amylase activity in the supernatant of cultured myeloma cells, obtained from the patient's pleural effusion while he had malignant pleuritis, increased almost linearly from the time of cell seeding. The presence of IgA and S-type amylase in the myeloma cells was demonstrated cytochemically and by immunoelectron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…Amylase production or secretion by malignant plasma cells was described in a small number of cases and demonstrated by immunohistochemical techniques and tissue culture [8,11,12]. Structural alterations and rearrangements involving chromosome 1 near the amylase locus were observed [9,12,13] and it seems possible that the amylase gene might be activated by an oncogene [10].…”
Section: Discussionmentioning
confidence: 99%
“…Amylase production or secretion by malignant plasma cells was described in a small number of cases and demonstrated by immunohistochemical techniques and tissue culture [8,11,12]. Structural alterations and rearrangements involving chromosome 1 near the amylase locus were observed [9,12,13] and it seems possible that the amylase gene might be activated by an oncogene [10].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Recently, a few new clinical features associated with myeloma, such as salivary type hyperamylasemia [7][8][9][10][11][12][13] and elevation of the serum Creactive protein (CRP) concentration [14][15][16] and oncostatin M, 17 have been reported. Elevation of CRP is thought to be related to interleukin-6 (IL-6) production by myeloma cells, because of the identification of IL-6 as an autocrine and/or paracrine growth factor for myeloma cells.…”
Section: Introductionmentioning
confidence: 99%
“…6 This patient had a A-IgA myeloma with extramedullary spread and died within 18 months of diagnosis. The amylase isoenzyme was the S type and this appears to be the more common isoenzyme associated with tumours.…”
Section: Discussionmentioning
confidence: 98%
“…Further evidence against macroamylasaemia was the normal urinary amylase/ Table 1. Amylase-producing myeloma -a review of cases reported in the literature Source Hata et al 6 Kanno et al 7 Proc. 30 th annual meeting Japanese Clinical Hematological SocietyB Wada et al 9 Tagawa et a/.…”
Section: Discussionmentioning
confidence: 99%